2010
DOI: 10.3758/lb.38.2.160
|View full text |Cite
|
Sign up to set email alerts
|

The derived generalization of thought suppression

Abstract: Thought suppression appears to be a relatively ineffective and even counter-productive strategy for dealing with unwanted thoughts. However, the psychological processes responsible for unsuccessful suppression are still underspecified. One process that may be implicated is derived stimulus relations, which may underlie the formation of unintentional relations that act to hamper suppression attempts. To test this prediction, participants were trained and tested for the formation of three derived equivalence rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…For example, in Augustson et al (1997), participants trained to avoid a stimulus correlated with shock also showed avoidance of stimuli in derived equivalence relations with the conditioned stimulus. Hooper et al (2010) demonstrated how the phenomenon of transfer of function through derived equivalence relations could make thought suppression less successful (i.e., as per our discussion above, of relatively shorter duration). These authors referred to the phenomenon whereby certain stimuli could make thought suppression less successful as 'interference' with thought suppression.…”
Section: Transfer Of Thought Suppression Via Same and Oppositementioning
confidence: 99%
See 4 more Smart Citations
“…For example, in Augustson et al (1997), participants trained to avoid a stimulus correlated with shock also showed avoidance of stimuli in derived equivalence relations with the conditioned stimulus. Hooper et al (2010) demonstrated how the phenomenon of transfer of function through derived equivalence relations could make thought suppression less successful (i.e., as per our discussion above, of relatively shorter duration). These authors referred to the phenomenon whereby certain stimuli could make thought suppression less successful as 'interference' with thought suppression.…”
Section: Transfer Of Thought Suppression Via Same and Oppositementioning
confidence: 99%
“…Furthermore, evidence provided by Hooper, Saunders and McHugh (2010) indicates that this phenomenon may play a critically important role in making thought suppression unsuccessful and thus current theories of the latter such as Wegner's ECH need to take it into account.…”
Section: Transfer Of Thought Suppression Via Same and Oppositementioning
confidence: 99%
See 3 more Smart Citations